ANALISIS DESKRIPTIF PETA KONFLIK UMAT BERAGAMA DI SUMATERA UTARA - Arifinsyah, Arifinsyah (UIN Sumatera Utara Medan, 2018)
The one hand, religion can be a far cry from the man who oppressed. On the other hand, religion can also be a faithful companion of those who are in pain, the loneliness and the loss of self esteem. Great historical facts show the alleged involvement of religion in many conflicts of mankind. At present, here and there, religious people do anarchism, repel and kill worshipers, terrorists and bomb blasts that killed many people, the tyranny of the ruler to his people, fighting over natural resources, racism, and arson. Why does this happen?, Any conflicts that occurred in North Sumatra?, And how prevention efforts?. This is what makes the writer interested to investigate further the conflict in Sumatra by using the method of observation conducted last five years. Hypothesis while showing that many conflicts are motivated by three fundamental things, namely; seizing the economic resources, political friction, and blasphemy. While conflicts are horizontal and vertical, inter-religious and religious people with a ruler or the State apparatus.